Stellar feedback and resolved stellar IFU spectroscopy in the nearby spiral galaxy NGC 300 - McLeod, Anna F.; Kruijssen, Diederik; Weisz, Daniel R.; Zeidler, Peter; Schruba, Andreas; Dalcanton, Julianne J.; Longmore, Steven N.; Chevance, Mélanie; Faesi, Christopher M.; Byler, Nell (The astrophysical journal, 2020)
We present MUSE integral field unit (IFU) observations of five individual H ii regions in two giant star-forming complexes in the low-metallicity, nearby dwarf spiral galaxy NGC 300. In combination with high spatial resolution Hubble Space Telescope photometry, we demonstrate the extraction of stellar spectra and classification of individual stars from ground-based IFU data at the distance of 2 Mpc. For the two star-forming complexes, in which no O-type stars had previously been identified, we find a total of 13 newly identified O-type stars and 4 Wolf-Rayet stars (two already-known sources and two Wolf-Rayet star candidates that this work has now confirmed). We use the derived massive stellar content to analyze the impact of stellar feedback on the H ii regions. As already found for H ii regions in the Magellanic Clouds, the dynamics of the analyzed NGC 300 H ii regions are dominated by a combination of the pressure of the ionized gas and stellar winds. Moreover, we analyze the relation between the star formation rate and the pressure of the ionized gas as derived from small (<100 pc) scales, both quantities being systematically overestimated when derived on galactic scales. With the wealth of upcoming IFU instruments and programs, this study serves as a pathfinder for the systematic investigation of resolved stellar feedback in nearby galaxies, delivering the necessary analysis tools to enable massive stellar content and feedback studies sampling an unprecedented range of H ii region properties across entire galaxies in the nearby universe.
Gesehen am 12.11.2020